The Authority of The Civil Judge in The Interrogation as Indirect Evidence of Proof: An analytical study - Shwan Omer Khalil; Karzan Rasul Hassan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
As it is clear, that the Iraqi law, represented by the evidences mentioned in the Iraqi evidence law No.107 of the year 1979 and its amendments, has given a wide area to the parties in a civil claim to be able to prove their rights on each other. At the same time, the same law gave the judge in such a claim a wide authority in directing the case and the evidences related to it to ensure the proper application of the law. Among these evidences mentioned in the Iraqi Evidence Law is the subject of (interrogation), which is the discussion of the litigants by the judge, in particular during the pleading of the case, and when there is no any complete denial of the matter of the dispute.In this research we have tried to focus a light upon this evidence and its role in providing the facts related to the case, which we think that , in such a claim the best thing to be done is to confront the questioned litigant in the presence of his opponent with the apparent facts that may prove the claim or the defence in order to achieve the justice.